Accountant Profession Responding To Impact Worse In Economic Conditions. - Usep Mahmud; Sugito Sugito (JIMF (Jurnal Ilmiah Manajemen Forkamma), 2020)
The economic crisis has already  general some audit risks. Audit practices become more complex. Going concern issues, ligitation toward accounting profession, changes in laws and regulation  affecting the profession have created the risk environment. Accounting profession  responses such changes by managing them properly to aproaches that are used to mitigate such risks are the comprehensive approach, and the appropriate policies and procedures approach. Moreover Indonesian Accountant Association as a standart board Authority has issued some PSAK ( Indonesian GAAP ) and SPAP ( Indonesia GAAS ) to provide the guidance  for implementing audit engagement in the risk environment.